2020
DOI: 10.1016/j.ajpath.2019.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 5 Signaling Ameliorates Liver Fibrosis by Inducing Interferon β–Modulated IL-1 Receptor Antagonist in Mice

Abstract: Bacterial flagellin, recognized by cell surface of Toll-like receptor (TLR) 5, is a potent activator of many types of cells, leading to the activation of innate or adaptive immunity, which are pivotal in regulating fibrotic process. However, the exact role of TLR5 signaling in hepatic fibrogenesis remains unclear, and this study aims to elucidate its underlying mechanisms. Flagellin was injected to hepatotoxin-and cholestasis-induced liver fibrosis murine models. Flagellin-induced TLR5 activation significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 47 publications
5
17
2
Order By: Relevance
“…7,22 So far, TLR5, the receptor for bacterial flagellin, has been implicated in progression of liver disease mainly in animal models. 23,24 In viral hepatitis B, the TLR5 rs5744174 TT genotype has been associated with HBe antigen to anti-HBe seroconversion, 25 with development of HCC in HBe antigen positive patients, 26 but also independently of HBe antigen status, 27 indicating that TLR5 21 our data support a hypothesis that flagellin is translocated from the intestine in cirrhotic patients and triggers via TLR5 an immune response favouring HCC development.…”
Section: Discussionsupporting
confidence: 72%
“…7,22 So far, TLR5, the receptor for bacterial flagellin, has been implicated in progression of liver disease mainly in animal models. 23,24 In viral hepatitis B, the TLR5 rs5744174 TT genotype has been associated with HBe antigen to anti-HBe seroconversion, 25 with development of HCC in HBe antigen positive patients, 26 but also independently of HBe antigen status, 27 indicating that TLR5 21 our data support a hypothesis that flagellin is translocated from the intestine in cirrhotic patients and triggers via TLR5 an immune response favouring HCC development.…”
Section: Discussionsupporting
confidence: 72%
“…By autophosphorylation, AKT1 regulates key signaling pathways such as the Janus kinase-signal transducer and activator of transcription (JAK-STAT), apoptosis, mammalian target of rapamycin, and mitogen-activated protein kinase (MAPK) signaling pathways [33,34], regulates apoptosis and related proteins, thus affecting the process of LF. IL-1β, a critical mediator of the inflammatory response, and can promote the proliferation and differentiation of HSCs in a dosedependent manner, leading to the occurrence and development of LF [35,36]. rough qPCR, we confirmed that SCJPF can downregulate the expression of IL-6, TP53, AKT1, and IL-1β in the pathogenesis of LF to play a role in the treatment of LF.…”
Section: Discussionsupporting
confidence: 53%
“…Tissues were harvested and lysed in cold extraction buffer (RIPA, Beyotime Biotechnology, Shanghai, China) as previously described [14]. Samples were centrifuged at 13,000 × g at 4°C for 15 min, and the protein concentration in the supernatants was measured using the Pierce BCA Protein Assay kit (Thermo Fisher Scienti c Inc., Waltham, IL, USA) according to the manufacturer's protocol.…”
Section: Western Blotmentioning
confidence: 99%